Analisis dan Perancangan Sistem Informasi Penjualan Online pada Perusahaan PT. Asuransi Jiwa Manulife Indonesia (e-Commerce B2C) - , Apriantini Fiqih; , Prof. Dr. Jogiyanto Hartono, MBA., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT. Asuransi Jiwa Manulife Indonesia (AJMI) is one of the largest life insurance company in Indonesia. Menulife Indonesia currently has four distribution channels, which is agency, corporate distribution, bancassurance, and direct marketing/tele marketing. To support its marketing and sales agent activities, Manulife Indonesia has implemented an online information system that accessible anywhere and anytime that spesifically to support the agent mobility. Although it has been utilizing the intenet to support agency operations, the sales of insurance products is still limited to the range of agents. Therefore, Manulife Indonesia needs an online information system that can be directly accessed by the customer (business to consumer) to extend the range of marketing and sales of insurance products that for later is expected to increase the companyâs competitive advantage. This study aims to analyze and design online sales information system (ecommerce B2C) using the method of application development FAST (Framework for the Application of System Thinking). Data collected by conducting interviews, direct observation, and companyâs documentation are then analyzed to obtain necessary information as to what information system design that fits company needs. The final result of this study is the logical design of online sales information system that consist of business processes, databases, and system arhitecture.